Neurophysiologic Detection of Spinal Cord Ischemia During Anterior Vertebral Tethering. Issue 24 (15th December 2020) - Clark, John Patrick; Diab, Mohammad
Abstract : Study Design: Case report. Objective: The aim of this study was to present how computed tomographic angiography (CTA) and intraoperative neurophysiologic monitoring (IONM) detect spinal cord ischemia during anterior spine surgery. These data directed expedient surgical and anesthetic interventions that restored IONM signals and prevented neurologic sequalæ. Summary of Background Data: Anterior vertebral tethering (AVT) is a fusionless surgical treatment of adolescent idiopathic scoliosis (AIS). Methods: AVT was performed on a skeletally immature patient with AIS. Preoperative CTA detailed location of the dominant radicular artery (DRA). Transcranial motor (tcMEP) and somatosensory (SEP) evoked potentials were monitored during operation. Results: There was significant decline in tcMEP, but not SEP, after compression of the DRA during cable tensioning of AVT. There was complete tcMEP recovery following release of instrumentation. Conclusion: This article identifies a rare but potentially catastrophic vascular hazard associated with anterior spine operation, including AVT. Sacrifice of multiple unilateral segmental vessels may overwhelm the capacity of collateral spinal cord perfusion to compensate for DRA blood supply. This vascular risk may be eliminated by identifying the DRA in order that it may be preserved during the procedure. Level of Evidence: 5 Abstract : This case details intraoperative neurophysiologic detection of spinal cord ischemia in a patient who underwent anterior vertebral tethering for idiopathic scoliosis with. Spinal cord perfusion and neural signals were restored by releasing the tethering cable that compressed the left T11 dominant radicular artery.